The Cambodian Elections and the Benefits of Legitimacy - Vu, Nhan T. (Tufts Archival Research Center, 2005)
Volume 20, Issue 1. Winter/Spring Years of war left Cambodia with a culture of endemic political violence. Elections may have broken that cycle and re-empowered the people.